Blacks, Reds, and Russians : sojourners in search of the Soviet promise - Carew, Joy Gleason (New Brunswick, N.J. : Rutgers University Press, 2008)
"One of the most compelling, yet little known stories of race relations in the twentieth century is the account of blacks who chose to leave the United States to be involved in the Soviet Experiment in the 1920s and 1930s. Frustrated by the limitations imposed by racism in their home country, African Americans were lured by the promise of opportunity abroad. A number of them settled there, raised families, and became integrated into society. The Soviet economy likewise reaped enormous benefits from the talent and expertise that these individuals brought, and the all around success story became a platform for political leaders to boast their party goals of creating a society where all members were equal. In Blacks, Reds, and Russians, Joy Gleason Carew offers insight into the political strategies that often underlie relationships between different peoples and countries. She draws on the autobiographies of key sojourners, including Harry Haywood and Robert Robinson, in addition to the writings of Claude McKay, W.E.B. Du Bois, and Langston Hughes." -- Book jacket.
A journey begins -- Early sojourners Claude McKay and Otto Huiswood : shaping the "Negro question" -- Harry Haywood, Kutva, and training black cadres -- W.E.B. Du Bois and the Soviet experiment -- Robert Robinson and the technical specialists -- George Washington Carver, Oliver Golden, and the Soviet experiment -- The agricultural specialists journey to the Soviet Union -- Langston Hughes and the black and white film group -- Paul Robeson's search for a society free of racism -- The expatriates : the purges, the war years, and beyond -- William "Bill" Davis, the American national exhibit, and U.S. public diplomacy -- The Cold War, solidarity building, and the recruitment of new sojourners.
Includes bibliographical references (p. 219-263) and index.
Keywords: African Americans -- Soviet Union -- History; African Americans -- Soviet Union -- Biography; African American intellectuals -- Soviet Union -- Biography; African American scientists -- Soviet Union -- Biography; Visitors, Foreign -- Soviet Union -- History; Intercultural communication -- Soviet Union; Soviet Union -- Race relations; Soviet Union -- Intellectual life -- 1917-1970.; Soviet Union -- Relations -- United States; United States -- Relations -- Soviet Union